Pendampingan Pencatatan Laporan Keuangan UMKM pada Usaha Dagang Anjas Desa Munerana Kecamatan Hewokloang - Elisabeth Susanti; Wea, Lasitania Azi; Floriance Astriana Pagan (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
This community service activity aims to help commercial business actors understand the basics and procedures for carrying out good recording and bookkeeping and can prepare financial reports. Based on the results of observations made by trading businesses, they do not understand the preparation of financial reports. The methods used in this community service are direct observation and interviews in the form of explanations about recording manganese trading business reports. It is hoped that this community service activity can help commercial business actors in recording and preparing correct financial reports. Business actors are expected to be able to manage their business finances well and implement financial report recording in accordance with accounting